Structure basis for C-C chemokine receptor 4 modulation by orthosteric and allosteric antagonists - Ning Zhou; Rong Wang; Baozhi Chen; Xiaofeng Qi (Proceedings of the National Academy of Sciences, 2026)
The chemokine system, comprising a network of chemokines and their receptors, orchestrates leukocyte migration and plays a central role in immune surveillance and inflammation. Targeting this system has emerged as a promising strategy in cancer immunotherapy and the treatment of immune-related disorders. C-C chemokine receptor 4 (CCR4), the receptor for chemokines CCL17 and CCL22, is a clinically validated therapeutic target for adult T cell leukemia/lymphoma, cutaneous T cell lymphoma, and other malignancies; however, the molecular mechanisms underlying CCR4 inhibition remain poorly understood. Here, we report five cryoelectron microscopy structures of human CCR4 in its apo state and in complex with four inhibitors. Tivumecirnon (FLX475) and Zelnecirnon (RPT193), two clinical-stage investigational drugs, bind to the orthosteric site of CCR4, blocking the chemokine recognition site 1. In contrast, AZD2098 and GSK2239633A occupy an allosteric site near the TM7–H8 turn, presumably interfering with G-protein coupling. Further analyses reveal that the therapeutic antibody mogamulizumab binds to the N-terminal region of CCR4 without competing with CCL17, suggesting that its antagonistic effect is mediated exclusively through antibody-dependent cellular cytotoxicity. Together, these structural insights elucidate distinct modes of CCR4 inhibition and provide a framework for the rational design of next-generation therapeutics targeting chemokine receptors.